Bone marrow mesenchymal stem cells (BMSCs) improved functional recovery of spinal cord injury partly by promoting axonal regeneration. (May 2018) - Lin, Liya; Lin, Hefeng; Bai, Shi; Zheng, Lianshun; Zhang, Xiaoming
Abstract: Spinal cord injury (SCI) disrupts the spinal cord and results in the loss of sensory and motor function below the lesion site. The treatment of SCI became a challenge because the injured neurons fail to axon regenerate and repair after injury. Promoting axonal regeneration plays a key role in the treatment strategies for SCI. It would meet the goal of reconstruction the injured spinal cord and improving the functional recovery. Bone marrow mesenchymal stem cells (BMSCs) are attractive therapeutic potential cell sources for SCI, and it could rebuild the injured spinal cord through neuroprotection, neural regeneration and remyelinating. Evidence has demonstrated that BMSCs play important roles in mediating axon regeneration, and glial scar formation after SCI in animal experiments and some clinical trials. We reviewed the role of BMSCs in regulating axon regeneration and glial scar formation after SCI. BMSCs based therapies may provide a therapeutic potential for the injured spinal cord by promoting axonal regeneration and repair. Graphical abstract: Abstract graphy, potential therapeutic promise of BMSCs on spinal cord injury. BMSCs could improve neuron regeneration by vascular repair, differentiating into neurons, inhibiting neuron apoptosis and necrosis, anti-inflammatory effects, improving sensitivity to glutamate ligands, neurotrophic active effect, reducing the glial scar. Highlights: Promoting axonal regeneration play a key role in the treatment strategies for SCI. BMSCs are very attractive therapeutic potential cell sources for SCI. BMSCs play important roles in mediating axon regeneration.